Nurses and midwives in Nazi Germany : the "euthanasia programs" - Benedict, Susan 1943- Hrsg; Shields, Linda (Routledge studies in modern European history, 2014)
"This book is about the ethics of nursing and midwifery, and how these were abrogated during the Nazi era. Nurses and midwives actively killed their patients, many of whom were disabled children and infants and patients with mental (and other) illnesses or intellectual disabilities. The book gives the facts as well as theoretical perspectives as a lens through which these crimes can be viewed. It also provides a way to teach this history to nursing and midwifery students, and, for the first time, explains the role of one of the world's most historically prominent midwifery leaders in the Nazi crimes"--